IRON DEFICIENCY ANAEMIA AMONG PRE-SCHOOL CHILDREN WITH SICKLE CELL ANAEMIA: STILL A RARE DIAGNOSIS? - Olufemi Samuel Akodu; Omolara Adeolu Kehinde; Ijeoma Nnena Diaku-Akinwumi; Olisamedua Fidelis Njokanma (Mediterranean Journal of Hematology and Infectious Diseases)
Background: The frequent need for blood transfusion in children with SCA creates the impression that IDA is rare in this class of children.